A study on the feasibility of implementing a quality management system, based on the EFQM model in a School of Engineering - Santos, Ricardo (2019)
Introduction: Currently, and in a competitive context, Higher Education Institutions (HEIs) increasingly depend on the quality of their services, not only to satisfy their different stakeholders, but also to attract funding. In this way, HEIs tend to incorporate Internal Quality Management Systems (IQMS) into their strategy with a view to the continuous improvement of their performance. This work intends to analyze the applicability of an HEI, based on the European Foundation for Quality Management (EFQM) model, through its implementation in a public Portuguese HEI. Objectives: Contribute to a critical analysis of the applicability of an IQMS in the organizational performance of an HEI, based on the EFQM model, and implemented in a published HEI. Methods: A number of advantages and difficulties were obtained. For the difficulties obtained, it was proposed a set of suggestions for its overcoming. Results: A number of advantages and difficulties were obtained. For the difficulties obtained, it was proposed a set of suggestions for its overcoming. Conclusions: The application of the SIGQ in the HEI under study, proved to be beneficial, due to a set of perceived advantages, among them, the increase of the organizational efficiency. For each one of the disadvantages identified in the study, a set of solutions was proposed for its mitigation, thus allowing to reinforce the potential of applying the EFQM model in an HEI.